1992
DOI: 10.1016/0014-5793(92)80174-f
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of FcγRIII mRNA in leukemic granulocytes

Abstract: Morphologically mature granulocytes from patients with chronic myeloid leukemia show significant impairment in their ability to internalize aggregated IgG, a ligand that is rapidly phagocytosed by normal human granulocytes. With a view to understand the molecular basis of this defect, normal and leukemic granulocytes were examined for the steady-state levels ofmRNA for Fc?'RIIL a memb=are-associat~xl receptur that initially binds and traps the !gG-opsonized antigens. Northern blot analyses revealed that the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…We would like to emphasize that the results reported here were found in patients receiving low dosage of rhG-CSF (5 g/ kg/d), whereas the only previous study performed on this topic (Spiekerman et al, 1994) did not show any inhibition with dosages ranging from 2 to 5 g/kg/d but only with dosages 4-20 times higher (in the agarose method). Similarly, a statistically significant reduction in the surface expression of CD16 -which may be an expression of abnormal neutrophil maturation Monteiro et al, 1992) -was found, by Spiekermann et al (1994), with high rhG-CSF dosages, whereas this molecule was found unchanged in our seven patients after low-dosage rhG-CSF treatment . So it may be that, apart from the unimportant number of band cells, rhG-CSF-induced PMN are 'morphologically' mature, but 'structurally' altered, because of the short maturation time.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We would like to emphasize that the results reported here were found in patients receiving low dosage of rhG-CSF (5 g/ kg/d), whereas the only previous study performed on this topic (Spiekerman et al, 1994) did not show any inhibition with dosages ranging from 2 to 5 g/kg/d but only with dosages 4-20 times higher (in the agarose method). Similarly, a statistically significant reduction in the surface expression of CD16 -which may be an expression of abnormal neutrophil maturation Monteiro et al, 1992) -was found, by Spiekermann et al (1994), with high rhG-CSF dosages, whereas this molecule was found unchanged in our seven patients after low-dosage rhG-CSF treatment . So it may be that, apart from the unimportant number of band cells, rhG-CSF-induced PMN are 'morphologically' mature, but 'structurally' altered, because of the short maturation time.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, a statistically significant reduction in the surface expression of CD16 -which may be an expression of abnormal neutrophil maturation Monteiro et al, 1992) -was found, by Spiekermann et al (1994), with high rhG-CSF dosages, whereas this molecule was found unchanged in our seven patients after low-dosage rhG-CSF treatment . So it may be that, apart from the unimportant number of band cells, rhG-CSF-induced PMN are 'morphologically' mature, but 'structurally' altered, because of the short maturation time.…”
Section: Discussionmentioning
confidence: 76%